THE INFLUENCE OF DOUBLE IMMUNIZATION ON MORBIDITY OF MEASLES, MUMPS AND RUBELLA IN THE NORTH-WEST REGION OF RUSSIA - L. V. Lyalina (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. The influence of double immunization on measles, mumps and rubella incidence in the North-West Federal District (North-West) Russia has been analyzed. Due to the vaccination of the population morbidity of these infections in the region has decreased significantly. The necessity to improve the surveillance system due to changes in the manifestations of the epidemic process particularly connected with increasing of proportion of adults among patients has been proposed.